Tips of the iceberg: domestic violence during COVID-19, Movement Control Order (MCO) in Malaysia - Tengku Zainal Mulok, Tengku Adida; Abdul Rahman, Hamizah; Nadarajan, Ravindran; Mohd. Zain, Nor Razinah (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Domestic violence can be defined as physical or emotional abuse of family members for many reasons, such as finances, drug abuse, jealousy, or other reasons that can result in injury or even the death of the victim. This paper explores several “tips of the iceberg” situations, which reflect cases of domestic violence during the COVID-19 Movement Control Order (MCO). This study was conducted primarily through a doctrinal study in elucidating relevant documents that comprised statutory laws and articles in legal journals. This paper also addresses the sufficiency of legal rules and regulations for protecting domestic violence victims. Lastly, the result of this study identified future initiatives to assist domestic violence victims.